The Antiinflammatory Action and Pharmacokinetics of a Novel Glucosamine-based Di-Peptide Aminosugar - Mohammad H. Gilzad-Kohan; Kamaljit Kaur; Fakhreddin Jamali (Frontiers Media S.A., 2013)
Purpose. We have previously shown favorable in vitro gut permeability for three novel di-peptide esters of glucosamine (GlcN) likely facilitated by the peptide transporter 1 (PepT1). Herein, we report the development of a novel assay for the determination of bioavailability of the peptide ester of interest, the anti-inflammatory properties of a glycine-valine ester derivative of GlcN (GVG) as well as its pharmacokinetics under healthy and inflammatory conditions. Methods. A pre-column derivatization (with 9-fluorenylmethoxycarbonyl) HPLC assay was developed to study bioavailability of GVG, GlcN or cleaved GlcN in the rats that were cannulated in their right jugular vein for blood collection. The compounds of interest were orally administered to both healthy and arthritic rats. Serial blood samples and urine were collected and assayed for the compounds. The stability of the GVG was also tested after incubation with the rat feces. Efficacy of GVG was tested in inflamed rats (injection of 0.2 mL of Mycobacterium butyricum in squalene) following GVG (20 and 30 mg/kg/day GlcN equivalent) or GlcN (20 and 90 mg/kg/day) administration. Arthritis index was calculated at the end of the experiment. Results. The assay was linear (ranged between 0.05-20 μg/mL) and reproducible (intra- and inter-day<10%). Among the tested compounds, only GVG showed a significantly higher plasma concentrations and urinary excretion than GlcN (≈3-fold increase). GVG showed a favorable stability in the rat feces. Adjuvant arthritis was completely prevented with doses greater than 20 mg/kg/day with GVG being 3-fold more potent than GlcN. Conclusion. The examined glycine-valine-GlcN di-peptide aminosugar is a potent anti-inflammatory compound due to its favorable properties to deliver GlcN into the systemic circulation. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.